2012
DOI: 10.1007/s10549-012-2198-y
|View full text |Cite
|
Sign up to set email alerts
|

Local estrogen therapy and risk of breast cancer recurrence among hormone-treated patients: a nested case–control study

Abstract: Women with estrogen-positive breast cancers receive endocrine treatment such as tamoxifen and aromatase inhibitors (AI) for 5-10 years. An important side effect of these drugs is vaginal dryness for which local hormonal therapy (LHT) represents the most effective treatment but is theoretically contraindicated. This study aimed to assess whether the use of LHT increases the risk of breast cancer recurrence among women receiving endocrine treatment. We conducted a cohort study with nested case-control analysis u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(62 citation statements)
references
References 24 publications
0
60
1
1
Order By: Relevance
“…Compared with previously published data for the general population, the overall incidence of adverse outcomes associated with vaginal estrogen use was low 13 14 17 34. Prior studies have not demonstrated that local vaginal estrogen increases the incidence of embolic events 13–19. Similarly, in this series, the incidence of deep venous thromboembolism and pulmonary embolism is low at 1.6%.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Compared with previously published data for the general population, the overall incidence of adverse outcomes associated with vaginal estrogen use was low 13 14 17 34. Prior studies have not demonstrated that local vaginal estrogen increases the incidence of embolic events 13–19. Similarly, in this series, the incidence of deep venous thromboembolism and pulmonary embolism is low at 1.6%.…”
Section: Discussioncontrasting
confidence: 66%
“…In the general population, vaginal estrogen has been proven safe and efficacious 15 17. Furthermore, in women with breast cancer, including estrogen receptor-positive tumors, vaginal estrogen use does not increase risk of recurrence 18 19. To date, use of vaginal estrogen in women with a history of gynecologic cancer has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Data regarding the safety of vaginal estrogen therapy in breast cancer survivors are limited. A case–control study of 271 women with breast cancer on tamoxifen or aromatase inhibitors concluded that there is no increased risk of recurrence in women on vaginal estrogen therapy, with a mean follow‐up of 3.5 years . In a retrospective cohort study, 60 women with early‐stage breast cancer were treated with an estradiol tablet or estriol cream for a median of 1 year.…”
Section: Treatmentmentioning
confidence: 99%
“…128 However, evidence suggests that local estrogen does not increase the risk of breast cancer recurrence. 129 Vaginal estrogen preparations include rings, suppositories, and creams, and they have been shown to be effective for managing symptoms of vaginal dryness in menopausal women. 127,130 Limited data in breast cancer survivors suggest minimal systemic absorption with rings and suppositories and are therefore preferred for survivors with hormone-sensitive tumors if estrogen-based treatment is warranted.…”
Section: Menopausementioning
confidence: 99%